Sosialisasi Door To Door Digital Marketing UMKM Desa Sumberjo - Tegar Satria Adi; Ira Wikartika (Universitas Muhammadiyah Manado, 2023)
Sumberjo Village as a tourist village that is rich in natural resources, ultimately encourages the formation of various kinds of MSMEs. However, until now, the knowledge of MSMEs regarding the use of social media and digital marketing is still considered lacking. Some MSMEs still apply conventional methods in marketing so that the profits and market reach they get are not optimal. The purpose of this activity is to provide understanding to MSME actors in Sumberjo Village about digital marketing procedures to help MSME players expand their market so they can compete with competitors. This activity was carried out through door-to-door socialization with several stages of the method including observation and interviews, lectures and discussions, as well as demonstrasions and practices. Communities need to be equipped with the basics and equipped with knowledge of the use of digital marketing so that development and increased sales can be realized as well as expectations as an MSME-friendly tourist village.